Posterior capsular calcification without opacification of intraocular lens - Joshi, Rajesh S (Nepalese Journal of Ophthalmology, 2016)
Background: Posterior capsular clarity is important for long-term visual gain. Postoperative visual acuity could be reduced due to posterior capsular or intraocular lens opacification, which occur months or years after cataract surgery. We report early occurrence of posterior capsular calcification without opacification of intraocular lens. Case: We report the case of a 78-year-old male who had undergone phacoemulsification with implantation of hydrophilic intraocular lens (IOL) in the left eye for cataract. The patient was non-diabetic, and the surgical procedure was uneventful. On the third postoperative day, fine granular deposits were found on the mid-peripheral part of the posterior capsule. No deposits were found on IOL. The patient presented with diminished vision four months after surgery. Slit-lamp examination revealed distinct areas of calcification with an early opacification of the posterior capsule and no IOL calcification. Neodymium doped: YAG capsulotomy was done to clear posterior capsular opacification, and the patient regained visual acuity of 20/20. To the best of our knowledge, this report is the first to investigate posterior capsular calcification without opacification of IOL in a patient without any known etiological factors. Conclusion: This case is reported to stimulate future study on the use of BSS plus and the development of posterior capsular or IOL calcification. Nepal J Ophthalmol 2016; 8(15): 91-94